Analisis Tingkat Kebutuhan Internet Terhadap Proses Pembelajaran E-Learning Siswa SMA Sederajat - Singgih Bektiarso; I Ketut Mahardika; Amalia Nurdina Sari; Harirotul Lathifah; Siti Silfi Farhana; Rosa Fahriatus Zahro (Peneliti.net, 2023)
The internet has a very significant influence on various aspects of life today, one of which is in the field of education, especially in e-learning. In the scope of the university the Internet is needed both by teaching staff and by students. So that the internet is very influential in the student learning process. This research will focus on how influential the internet needs are for students in the E-Learning process. The method used in this study is a qualitative research method with stages namely problem formulation, literature study, model formulation, instrument preparation, data collection, collection, and drawing conclusions. Based on the research that has been done, the result is that the internet is a very important and influential part of the E-Learning process, seeking scientific information, and forming student achievement.